Development of an energy-saving design for the feeding system of a concrete mixing plant - Korobko , Bogdan; Levchenko , Oleksandr; Rudyk , Rostyslav (Academic journal Industrial Machine Building Civil Engineering, 2023)
The study focuses on the development of an energy-saving design for concrete mixer mix components supply system to enhance efficiency and reduce environmental impact. The proposed changes to the schematic diagram include the implementation of separate hoppers with individual conveyors to optimize energy consumption and increase productivity. These modifications aim to improve energy efficiency, reduce material change time, and prevent congestion in the supply system, ultimately leading to enhanced productivity and streamlined production processes. This study highlights the importance of innovative design solutions in the feeding supply system of industrial plants to drive sustainability and efficiency improvements.
Keywords: concrete mixing plant; concrete mixer mix components supply system; energy efficiency; ecology; productivity; material change time; sustainability; concrete